The Theranostics Role of Mast Cells in the Pathophysiology of Rosacea - Wang, Lian; Wang, Yu-Jia; Hao, Dan; Wen, Xiang; Du, Dan; He, Gu; Jiang, Xian (Frontiers in Medicine, 2020)
Rosacea is a chronic inflammatory cutaneous disorder that adversely affects patient health and quality of life due to the complex course and the need for repeated treatment. The exact molecular mechanisms of rosacea are unclear. Mast cells are innate immune cells that can be found in virtually all tissues. Recently, increasing evidence has indicated that mast cells have important effects on the pathogenesis of rosacea. In this review article, we describe recent advances of skin mast cells in the development of rosacea. These studies suggested that mast cells can be an important immune cell that connected innate immune, nerves and blood vessels in the development of rosacea. Moreover, we review the inhibition of mast cells for the potential treatment of rosacea.